Medial circumflex femoral artery flap for ischial pressure sore - Palanivelu, S. (Medknow Publications, 2009)
A new axial pattern flap based on the terminal branches of the medial circumflex femoral artery is described for coverage of ischial pressure sore. Based on the terminal branches of the transverse branch of medial circumflex femoral artery, which exit through the gap between the quadratus femoris muscle above and the upper border of adductor magnus muscle below, this fascio cutaneous flap is much smaller than the posterior thigh flap but extremely useful to cover ischeal pressure sores. The skin redundancy below the gluteal fold allows a primary closure of the donor defect. It can also be used in combination with biceps femoris muscle flap.